Development of a Collaborative Exploratory Learning Model with Augmented Reality in Science: Pengembangan Model Pembelajaran Eksploratif Kolaboratif dengan Augmented Reality pada IPA - Illahi, Padmi Rohmatul; Hamdani, Nizar Alam; Nasrulloh, Iman (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Science education in the digital era requires innovative learning models that integrate technology to foster deeper understanding and engagement. Specific Background: Despite the growing application of Augmented Reality (AR) in classrooms, its integration into structured pedagogical models for junior high school science remains limited. Knowledge Gap: Existing research emphasizes AR’s benefits for visualization and interaction, yet there is no comprehensive model that combines exploratory, collaborative, and supportive approaches using AR, particularly for the topic of the Solar System. Aim: This study aims to develop and validate the EKSPLORS learning model supported by AR modules for seventh-grade science learning. Results: The model was developed using the Dick and Carey design framework and evaluated by instructional design, subject matter, and media experts, as well as through individual trials. Validation scores indicated high feasibility: 95% (instructional design), 86% (content), 89% (media), and 88% (student trials). Novelty: The model uniquely integrates exploration, collaboration, and scaffolding with AR-based visualization to enhance conceptual understanding of abstract scientific phenomena. Implications: Findings suggest that the EKSPLORS-AR model can significantly improve motivation, engagement, and comprehension in science education, offering a scalable innovation aligned with the Merdeka Belajar policy and digital transformation in Indonesian schools.Highlight : The EKSPLORS model with AR module was rated highly feasible by experts. This innovation helps students understand abstract science concepts interactively. The development follows the systematic steps of the Dick & Carey model. Keywords : EKSPLORS Learning Model, AR Module, Dick & Carey Development Model, Science Learning, Educational Technology